Healthy Eating: Strategies for Eating Alone - Emily Minton (EDIS)
Eating alone may not always be our first choice, but there are many ways to make eating alone more enjoyable. Can you find the strategies in this word search? Written by Emily Minton and published by the UF Department of Family, Youth and Community Sciences, March 2012.